Competing conceptualizations of decent work at the intersection of health, social and economic discourses. (May 2015) - Di Ruggiero, Erica; Cohen, Joanna E.; Cole, Donald C.; Forman, Lisa
Abstract: According to the International Labour Organization (ILO), decent work is critical to economic and social progress and well-being. The ILO's Decent Work Agenda outlines four directions (creating jobs, guaranteeing rights at work, extending social protection, promoting social dialogue) (ILO, 2015). While the Agenda's existence may imply consensus about its meaning, we contend that several conceptualizations of decent work exist in the global policy arena. Different institutional perspectives must be negotiated, and political, economic, social and health considerations balanced in its pursuit. This paper reports findings from a critical discourse analysis of 10 policy texts that aimed to reveal different health, economic, and social claims about decent work and how these are shaped by the work policy agendas of the ILO, World Health Organization, and World Bank. Themes emerging from the discourse analysis include the: challenges and realities of promoting "one" agenda; complex intersection between decent work, health and health equity concepts; emphasis on economic and pro-market interests versus the social dimensions of work; and, relative emphasis on individual versus collective responsibility for decent work. To our knowledge, this is a first attempt to contrast different conceptualizations of decent work involving these institutions. Our findings suggest that decent work is a contested notion, and that more than one "agenda" is operating in the face of vested institutional interests. Broader discourses are contributing to a reframing of decent work in economic, social and/or health terms and these are impacting which dimensions of work are taken up in policy texts over others. Results show how the language of economics acts as a disciplinary and regulatory power and its role as a normalizing discourse. We call for research that deepens understanding of how a social, economic and health phenomenon like work is discursively re-interpreted through different global institutional interests. Highlights: The language of economics and market-based solutions permeates several texts. Health equity principles about work are more present in ILO and WHO texts. Use of jobs over decent work reinforces discourses about who dominates work agendas. We noted shifts in ILO decent work frame to a World Bank frame post-economic crisis.